Potential drug–drug interactions in HIV-infected children on antiretroviral therapy in Lagos, Nigeria - Oshikoya KA (Dove Medical Press, 2014)
Kazeem A Oshikoya,1 Ibrahim A Oreagba,2 Saheed Lawal,2 Olufunsho Awodele,2 Olayinka O Ogunleye,1 Idowu O Senbanjo,3 Sunday O Olayemi,2 Veronica C Ezeaka,4,5 Edamisan O Temiye,4,5 Titilope A Adeyemo,4,6 Oluranti Opanuga,4,7 Olufunmilayo A Lesi,4,8 Sulaimon A Akanmu4,6 1Department of Pharmacology, Lagos State University College of Medicine, Ikeja, Lagos, Nigeria; 2Department of Pharmacology, College of Medicine, University of Lagos, Idi-Araba, Lagos, Nigeria; 3Department of Paediatrics, Lagos State University College of Medicine, Ikeja, Lagos, Nigeria; 4APIN Clinic, Lagos University Teaching Hospital, Lagos, Nigeria; 5Department of Paediatrics, College of Medicine, University of Lagos, Idi-Araba, Lagos, Nigeria; 6Department of Haematology and Blood Transfusion, College of Medicine, University of Lagos, Idi-Araba, Lagos, Nigeria; 7Department of Pharmacy, Lagos University Teaching Hospital, Idi-Araba Lagos, Nigeria; 8Department of Medicine, College of Medicine, University of Lagos, Idi-Araba, Lagos, Nigeria Background: Multi-therapy is common in HIV-infected children, and the risk for clinically significant drug interactions (CSDIs) is high. We investigated the prevalence of CSDIs between antiretroviral (ARV) and co-prescribed drugs for children attending a large HIV clinic in Lagos, Nigeria. Methods: The case files of pediatric patients receiving treatment at the HIV clinic of the Lagos University Teaching Hospital (LUTH), Idi-Araba, between January 2005 and December 2010 were reviewed. The ARV and co-prescribed drug pairs were evaluated for potential interactions using the Liverpool HIV Pharmacology Group website. The potential interactions were rated as A (no known interaction), B (minor/no action needed), C (moderate/monitor therapy), D (major/therapy modification), and X (contraindicated/avoid combination). Results: Of the 310 cases reviewed, 208 (67.1%) patients were at risk of CSDIs. Artemisinin-based combination therapy was prescribed for over one-half of the patients, accounting for 40% of the CSDIs. Excluding this drug class, the prevalence of CSDIs reduced from 67.1% to 18.7% in 58 patients. Most of the CSDIs (579; 97.2%) were moderately significant and frequently involved nevirapine and fluconazole (58; 9.7%), zidovudine and fluconazole (55; 9.2%), zidovudine and rifampicin (35; 5.9%), and nevirapine and prednisolone (31; 5.2%). Age (P=0.392), sex (P=0.783), and moderate (P=0.632) or severe (P=0.755) malnutrition were not associated with risk for CSDIs. Conclusion: There is a tendency for CSDIs between ARV and co-prescribed drugs among the group of children evaluated in this study. Measures are necessary to prevent important drug interactions and to manage those that are unavoidable. Keywords: infection, antiretroviral drug, co-prescribed drug, prevalence, therapy monitoring, therapy modification, contraindication